Scaling Up and Sustaining Innovation Policies and Projects : Schumpeterian Development Agencies in Small Open Economies - Breznitz, Dan; Ornston, Darius (World Bank, Washington, DC, 2017)
This paper examines how two historically low-technology economies, Finland and Israel, assumed leadership in new, rapid innovation-based industries. The paper argues that Schumpeterian development agencies, the Finnish Fund for Research and Development and the Israeli Office of the Chief Scientist in the Ministry of Trade and Industry played a transformative role, introducing new science and technology policies and facilitating industrial restructuring. In contrast to literature on the developmental state, however, argues that these agencies were located the periphery of the public sector, with few hard resources. The paper describes how their peripheral location facilitated successful experimentation. It also explains how ostensibly marginal agencies could successfully scale and monitor new initiatives. More specifically, it argues that reform-oriented policy-makers in small states could leverage extensive inter-personal networks to facilitate scaling and international openness to facilitate monitoring. In identifying specific mechanisms by which policy-makers introduced, scaled and monitored policies, it also explains why these two historically innovative economies have struggled to support experimentation in recent years.